Grazoprevir and Elbasvir in Patients with Genotype 1 Hepatitis C Virus Infection: A Comprehensive Efficacy and Safety Analysis. (9th January 2017) - Yao, Yinan; Yue, Ming; Wang, Jie; Chen, Hongbo; Liu, Mei; Zang, Feng; Li, Jun; Zhang, Yun; Huang, Peng; Yu, Rongbin
Abstract : Background. It is urgent for patients with hepatitis C virus (HCV) infection to find a safe, effective, and interferon-free regimen to optimize therapy. A comprehensive analysis was performed to evaluate the efficacy and safety of the grazoprevir combined with elbasvir, with or without ribavirin (RBV), in 777 treatment-naive and treatment-experienced patients with HCV genotype 1 infection from 3 randomized controlled trials (RCTs). Method. We collected data from the following trials: C-WORTHY (NCT01717326 ), C-SALVAGE (NCT02105454 ), and C-EDGE (NCT02105467 ). All patients received grazoprevir plus elbasvir with or without RBV for 12 or 18 weeks. The sustained virological response (SVR) 12 weeks after end of treatment was calculated for overall and subgroups. Results. 568 (73%) patients were treatment-naive. Overall, 95% (95% CI: 93–96) patients achieved SVR12, 95% (95% CI: 92–96) for treatment-naive and 96% (95% CI: 92–98) for previously treated patients, respectively. Treatment duration and treatment regimen did not have great difference in SVR12 rates. The most common AEs were fatigue (18%–29%), headache (20%), nausea (8%–14%), and asthenia (4%–12%). One patient (<1%) receiving grazoprevir plus elbasvir alone and one (<1%) receiving grazoprevir plus elbasvir plus RBV had treatment-related serious AEs. Conclusions. The result shows that 12-week grazoprevir plus elbasvir therapy is safe and effective for treatment-naive patients with HCV genotype 1.